The Role of Compatibility, Complexity, and Perceived Behavioral Control in Shaping Attitude Towards Innovation and Adoption of Performance-Based Budgeting in Iraq - Alkhuzaie, Rusul; Muhamad, Haslinah; Daud, Zaidi Mat; Senik, Rosmila (Advances in Social Sciences Research Journal, 2025)
The adoption of Performance-Based Budgeting (PBB) is a critical step toward enhancing transparency, efficiency, and accountability in public financial management. However, despite parliamentary support for PBB in Iraq, its implementation remains stalled. This study examines the factors influencing the intention to adopt PBB, focusing on compatibility, complexity, perceived behavioral control, and attitude toward innovation. The study integrates Diffusion of Innovation Theory (DOI) and Theory of Planned Behavior (TPB) to explore how these factors interact to shape financial officials’ decision-making processes. A structural equation modeling (SEM) approach was employed using survey data from 202 financial officials in Iraq’s Ministry of Finance and Ministry of Planning. The findings reveal that perceived behavioral control plays the most significant role in adoption intention, indicating that confidence in implementation capabilities is a key driver of PBB adoption. Complexity negatively influences adoption intention, suggesting that officials perceive PBB as challenging to implement, which discourages its uptake. Additionally, attitude toward innovation significantly mediates the relationships between complexity, perceived behavioral control, and PBB adoption intention, highlighting the importance of shaping positive perceptions of financial reforms. However, compatibility does not have a direct effect on adoption intention, suggesting that alignment with existing budgeting practices may not be a primary concern for financial officials. The study provides theoretical contributions by integrating behavioral and innovation adoption perspectives to explain public sector budgeting reforms. Practical implications highlight the need for capacity-building programs, institutional support, and simplified implementation guidelines to facilitate PBB adoption. The study recommends a phased rollout strategy, targeted training, and stakeholder engagement to overcome adoption barriers. Future research should explore political and organizational influences, cross-country comparisons, and longitudinal assessments to further understand the adoption dynamics of PBB. This research contributes to the ongoing dialogue on financial reform in Iraq, offering a framework for policymakers to enhance budget efficiency and accountability through performance-based financial management.